1876-77 N.C. Sess. Laws 53 - (:unkn) unknown (My University, 1877)
Ch. 4, §§ 1-2: That if any person shall cast, or throw, or shoot, any stone, rock, bullet, shot, pellet, or other missile, at, against, or into, any railroad car, locomotive, or train, while the said car or locomotive shall be in progress from one station to another, or while the said car, locomotive or train shall be stopped for any purpose, with intent to injure said car or locomotive, or any person therein or thereon, the person so offending shall be guilty of a misdemeanor, and, upon conviction thereof, shall be punished by fine or imprisonment in the county jail, or the State prison, at the discretion of the Court.
Keywords: COMMITTING CRIME W/ WEAPON